Alternating current and direct current generator - Portela, Pedro Miguel Dourado (2008)
Spinning a wire loop within a uniform magnetic field in a convenient fashion induces a voltage between the loop terminals. This effect can be used to build an electric power generator, such as the one described in this paper. A coil attached to a shaft spins within the magnetic field of a "U" shaped magnet. Three conveniently designed conductive disks allow the electrical load of the generator to be fed either with alternating current or direct current.